VD_FINDINFO HC / 2010 / 169 vom 11. März 2010 - VD Tribunal cantonal (2010)
DIVORCE, MAXIME OFFICIELLE ET INQUISITOIRE, DROIT DE GARDE, AUTORITÉ PARENTALE | 133 al. 1 CC, 138 al. 1 CC, 145 al. 1 CC, 374c CPC, 444 CPC, 445 CPC, 451 ch. 2 CPC, 452 al. 1ter CPC, 452 al. 2 CPC